The association between caries related treatment needs and socio-demographic variables among young Israeli adults: a record based cross sectional study - Dan Henry Levy; Alon Livny; Harold Sgan-Cohen; Nirit Yavnai (BMC, 2018)
Abstract Backgroud The need for dental treatments, especially those related to dental caries, may be associated with and influenced by a wide range of demographic variables. The aim of this study was to describe caries related treatment needs among young Israeli adults and the association with several socio-demographic factors, including socio-economic cluster (SEC), intellectual capabilities, ethnicity and other variables. Methods Data were collected from dental records of army recruits between 2012 and 2013. We cross-examined data regarding dental treatment needs with socio-demographic variables: age, gender, SEC, intellectual capability score (ICS), birth place of participant and parents, education and immigration. Results Data received regarding 13,398 combat recruits during their first four months of military training. Most subjects were males (92.4%), with a mean age of 18.9 years. 10.8% were immigrants, with 12.2 years living in Israel before their recruitment. Only 17.7% had no dental treatment needs. Mean number of teeth needing treatment was: for restorations 1.96 ± 2.59, for root canal therapies 0.07 ± 0.44 and for extractions 0.05 ± 0.28. Low ICS scores and low SEC group were significantly associated with higher treatment needs (P < 0.001). Statistically significant higher treatment needs were observed among participants who originated from immigrant families. In a multivariate analysis (Generalized Linear Model), gender, age, ICS score, SEC group and country of birth were found as independent predictors for number of restorations needed. Conclusion Socio-demographic variables significantly influence dental treatment needs and should be taken into account when preparing intervention programs in this population.